Managing of the Arctic Development: Financial Support of the Region and the Criteria Choice for Evaluating the Effectiveness of Investment Projects - V. A. Tsvetkov; M. N. Dudin; D. A. Еrmilina (Управленческие науки)
The article highlights the current problems of financial support for investment projects for the development of the Arctic. There is one of the most important factors in the implementation of such projects significant for the national economy should be a focus on the systematic development of the Arctic territories and the optimal development of its scientific and industrial potential. The full-scale implementation of such projects will provide a cargo flow increase across the Northern Sea route, that will affect positively on strategic positions of the russian economy, have being possessed one more perspective transit transport corridor. A research purpose is comprehensive study of the existing and perspective investment projects of the Arctic region development, to working-out on recommendations about the priority projects selection and assessment of their efficiency. The analysis of various federal programs and initiatives of the executive power of the Arctic shows the efficiency evaluation of investment projects of the region development and their selection should be based on indicators as commercial and budgetary, as well as the socio-economic efficiency of each project. Evaluation of each type of efficiency involves the use of a number of indicators from which the authors single out the most significant. Besides, the selection of the development investment projects of the Arctic region should consider the following criteria: coordination of project parameters, their consistency with the priorities of the Arctic state policy; specification of deadlines, amounts of funding, resources support and the presence of targeting in each project; definition of the target results of the project providing for the special (basic) zones formation in the Arctic development. Such approach provides a comprehensive assessment of each project from the point of feasibility view of implementing and obtaining the required results, which is going to be expressed in the sustainable scientific, industrial, economic and technological development of the russian Arctic. It is revealed that the assessment of the effectiveness of projects for the development of the Arctic region should be based on a set of indicators of commercial, socio-economic and budgetary efficiency. regulatory base assessment: methodological documents approved by the federal executive authorities, taking into account the peculiarities of the implementation of infrastructure projects based on various forms of public-private partnership. The stated above application assessment criteria for each individual Arctic project will allow optimal allocation of budget funding in the context of a shortage of public finances.